Intravaginal Testicular Torsion with Ureterocele: A Rare Case Report - Adnan Ilyas; Suresh Vasant Phatak; Avinash Parshuram Dhok; Swaragandha Shivaji Jadhav (Journal of Medical Ultrasound)
Testicular torsion is an emergency clinical situation. It is rarely seen associated with ureterocele. We presented a case report where a 15-year-old adolescent boy presented with severe testicular and vague abdominal pain was found on imaging to have testicular torsion and ureterocele. Ultrasonography Doppler and computed tomography imaging are being described.